Mechanical properties of low alloy high phosphorus weathering steel - Jena B.K.; Gupta N.; Singh B.; Ahoo G.S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Mechanical behaviour of two low alloy steels (G11 and G12) was studied with respect to different phosphorus contents. Tensile strength and yield strength increased while percentage elongation at fracture decreased on increasing phosphorus content. The SEM and light optical photomicrograph of low phosphorus steel (G11) revealed ferrite and pearlite microstructure. On increasing phosphorus content from 0.25 wt.% to 0.42 wt.%, the morphology of grain changed from equiaxed shape to pan-cake shape and grain size also increased. The Charpy V notch (CVN) impact energy of G11 and G12 steel at room temperature was 32 J and 4 J respectively and their fractographs revealed brittle rupture with cleavage facets for both the steels. However, the fractograph of G11 steel after tensile test exhibited ductile mode of fracture with conical equiaxed dimple while that of G12 steel containing 0.42 wt. % P exhibited transgranular cleavage fracture. Based on this study, G11 steel containing 0.25 wt. % P could be explored as a candidate material for weathering application purpose where the 20°C toughness requirement is 27 J as per CSN EN10025-2:2004 specification.